PEMBANGKITAN LISTRIK MENGGUNAKAN GENERATOR THERMOELECTRIC BERPENDINGIN KIPAS DENGAN MEMANFAATKAN PANAS KOMPOR GAS LPG - , ILYAS; , Sugianto, ST., M . Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Thermoelectric generator is a tool that converts heat energy into electric energy, generator Themoelectric applied on the stove so that traders can take advantage of electricity were generated thermoelectric energy generators. Thermoelectric module is a tool that converts heat energy from a temperature gradient into electrical energy or vice versa of the electrical energy into a temperature gradient. Many discussions usually revolve figure-of-Merit or ZT of thermoelectric materials and the impact on the efficiency of conversion of heat into electricity at thermoelectric generator applications or thermoelectric cooling. At the moment there is a difference in the field test data when testing using more efficient than kettles kettles do not use, because the temperature of heat generated by the stove is not much wasted, and more absorbed by the hot side of TEG.